The unobserved economy and the Dutch national accounts after the benchmark revision 2015 - Brugt Kazemier; Michel van Veen; Sander IJmker (Central European Economic Journal (CEEJ), 2019)
In 2018, Statistics Netherlands carried out a general benchmark revision of their national accounts statistics. The base year was 2015. Special attention was paid to the exhaustiveness of the estimates. Among other, these include estimates for illegal activities and tax evasion. In the first step, the main (illegal and off the record) activities that were not included in the regular data sources underlying the national accounts were identified. In the second step, estimates were made for each identified activity, based on the scarce information data sources available, supplemented with assumptions. This paper describes the second step. The value added of illegal activities in 2015 was estimated at 4.8 billion euros, which is 0.7% of gross domestic product (GDP). The explicit adjustment for tax evasion was about 3.9 billion euros, which is slightly <0.6% of GDP.
Keywords: E01; E26; 330; national accounts; illegal activities; tax evasion; underground economy